Studies on neotropical Phasmatodea XX: A new genus and 16 new species from French Guiana - Conle, Oskar V.; Hennemann, Frank H.; Bellanger, Yannick; Lelong, Philippe; Jourdan, Toni; Valero, Pablo (Zootaxa, 2020)
The present paper describes 16 new species and one new genus from French Guiana and numerous taxonomic changes are proposed prior to the publication of a comprehensive guide to the Phasmatodea of French Guiana. The following 16 new species are described and illustrated: Phanocles procerus n. sp., Phanocloidea lobulatipes n. sp., Cladomorphus guianensis n. sp., Hirtuleius gracilis n. sp., Parastratocles rosanti n. sp., Parastratocles fuscomarginatus n. sp., Paraprisopus apterus n. sp., Paraprisopus multicolorus n. sp., Agrostia longicerca n. sp., Isagoras similis n. sp., Paragrostia brulei n. sp., Prexaspes globosicaput n. sp., Prexaspes guianensis n. sp., Dinelytron cahureli n. sp., Prisopus clarus n. sp. and Prisopus conocephalus n. sp.. The new genus Paragrostia n. gen. is established for the newly described Paragrostia brulei n. sp. and Paragrostia flavimaculata (Heleodoro, Mendes & Rafael, 2017) n. comb. the latter of which is here transferred from Agrostia Redtenbacher, 1906. Fifty-six new combinations are proposed with species transferred to other genera: Bacteria pallidenotata Redtenbacher, 1908, is transferred to Phanocloidea Zompro, 2001 (n. comb.); Bacteria maroniensis Chopard, 1911 is transferred to Phanocles Stål, 1875 (n. comb.); Cladomorphus gibbosus (Chopard, 1911) is transferred to Hirtuleius Stål, 1875 (n. comb.); Stratocles soror Redtenbacher, 1906, Parastratocles lugubris (Redtenbacher, 1906) and Parastratocles cryptochloris (Rehn, 1904) are transferred to Brizoides Redtenbacher, 1906 (n. comb.); Stratocles xanthomela (Olivier, 1792), Stratocles forcipatus Bolívar, 1896 and Stratocles tessulatus (Olivier, 1792) are transferred to Parastratocles (n. comb.); Olcyphides cinereus (Olivier, 1792), Perliodes affinis Redtenbacher, 1906, Perliodes nigrogranulosus Redtenbacher, 1906, Perliodes sexmaculatus Redtenbacher, 1906, Isagoras rugicollis (Gray, 1835), Isagoras sauropterus Rehn, 1947, Brizoides viridipes (Rehn, 1905) and Brizoides graminea Redtenbacher, 1906 are transferred to Agrostia Redtenbacher, 1906 (n. comb.); Agrostia flavimaculata Heleodoro, Mendes & Rafael, 2017 is transferred to Paragrostia n. gen. (n. comb.); Isagoras affinis Chopard, 1911, Isagoras chocoensis Hebard, 1921, Isagoras metricus Rehn, 1947 and Isagoras schraderi Rehn, 1947 are transferred to Tenerella Redtenbacher, 1906 (n. comb.); Xerosoma glyptomerion Rehn, 1904 is transferred to Isagoras Stål, 1875 (n. comb.); Isagoras venosus (Burmeister, 1838), Paraphasma paulense Rehn, 1918 and Paraphasma quadratum (Bates, 1865) are transferred to Prexaspes Stål, 1875 (n. comb.); Prexaspes (Prexaspes) cneius (Westwood, 1859) is transferred to Tenerella Redtenbacher, 1906 (n. comb.); Prexaspes lateralis (Fabricius, 1775) is transferred to Paraphasma Redtenbacher, 1906 (n. comb.); Isagoras santara (Westwood, 1859) and Prexaspes olivaceus Chopard, 1911 are transferred to Periphloea Redtenbacher, 1906 (n. comb.); Dinelytron agrion Westwood, 1859 is transferred to Paraprisopus Redtenbacher, 1906 (n. comb.); Anarchodes atrophicus (Pallas, 1772) is transferred to Ignacia Rehn, 1904 (n. comb.); Planudes asperus Bellanger & Conle, 2013, Planudes brunni Redtenbacher, 1906, Planudes cortex Hebard, 1919, Planudes crenulipes Rehn, 1904, Planudes funestus Redtenbacher, 1906, Planudes melzeri Piza, 1937, Planudes molorchus (Westwood, 1859), Planudes paxillus (Westwood, 1859), Planudes perillus Stål, 1875, Planudes pygmaeus (Redtenbacher, 1906) and Planudes taeniatus Piza, 1944 are transferred to Isagoras Stål, 1875 (n. comb.); Prisopoides atrobrunneus Heleodoro & Rafael, 2020, Prisopoides brunnescens Heleodoro & Rafael, 2020, Prisopoides caatingaensis Heleodoro & Rafael, 2020 and Prisopoides villosipes (Redtenbacher, 1906) are transferred to Prisopus Peletier de Saint Fargeau & Serville, 1828 (n. comb.); Melophasma antillarum (Caudell, 1914), Melophasma brachypterum Conle, Hennemann & Gutiérrez, 2011, Melophasma colombianum Conle, Hennemann & Gutiérrez, 2011 and Melophasma vermiculare Redtenbacher, 1906 are transferred to Paraprisopus Redtenbacher, 1906 (n. comb.); Prexaspes (Elasia) ambiguus (Stoll, 1813), Prexaspes (Elasia) brevipennis (Burmeister, 1838), Prexaspes (Elasia) pholcus (Westwood, 1859), Prexaspes (Elasia) viridipes Redtenbacher, 1906 and Prexaspes (Elasia) vittata (Piza, 1985) are transferred to Prexaspes Stål, 1875 (n. comb.). Twenty-six new synonymies are established: Perliodes Redtenbacher, 1906 and Chlorophasma Redtenbacher, 1906 are synonymised with Agrostia Redtenbacher, 1906 (n. syn.); Chlorophasma Redtenbacher, 1906 is synonymised with Agrostia Redtenbacher, 1906 (n. syn.); Elasia Redtenbacher, 1906 is synonymised with Prexaspes Stål, 1875 (n. syn.); Prisopoides Heleodoro & Rafael, 2020 is synonymised with Prisopus Peletier de Saint Fargeau & Serville, 1828 (n. syn.); Melophasma Redtenbacher, 1906 is synonymised with Paraprisopus Redtenbacher, 1906 (n. syn.); Bacteria crassipes Chopard, 1911 is synonymised with Bacteria pallidenotata Redtenbacher, 1908 (n. syn.); Perliodes grisescens Redtenbacher, 1906 and Metriophasma (Metriophasma) pallidum (Chopard, 1911) are synonymised with Agrostia cinerea (Olivier, 1792) (n. syn.); Perliodes nigrogranulosus Redtenbacher, 1906 and Metriophasma (Metriophasma) ocellatum (Piza, 1937) are synonymised with Isagoras rugicollis (Gray, 1835) (n. syn.); Isagoras chopardi Hebard, 1933 is synonymised with Tenerella cneius (Westwood, 1859) (n. syn.); Isagoras proximus Redtenbacher, 1906 is synonymised with Isagoras glyptomerion (Rehn, 1904) (n. syn.); Chlorophasma hyalina Redtenbacher, 1906 is synonymised with Agrostia graminea (Redtenbacher, 1906) (n. syn.); Isagoras nitidus Redtenbacher, 1906 is synonymised with Anisa flavomaculatus (Gray, 1835) (n. syn.); Prexaspes acuticornis (Gray, 1835) is synonymised with Prexaspes servillei (Gray, 1835) (n. syn.); Prexaspes nigromaculatus Chopard, 1911 is synonymised with Periphloea santara (Westwood, 1859) (n. syn.); Prexaspes (Elasia) janus Kirby, 1904 is synonymised with Paraphasma maculatum (Gray, 1835) (n. syn.); Prexaspes dictys (Westwood, 1859) is synonymised with Prexaspes brevipennis (Burmeister, 1838) (n. syn.); Parastratocles aeruginosus Redtenbacher, 1906: 107 is synonymised with Parastratocles forcipatus Bolívar, 1896 (n. syn.); Parastratocles carbonarius (Redtenbacher, 1906: 106) is synonymised with Parastratocles lugubris (Redtenbacher, 1906) (n. syn.); Prisopus spinicollis Burmeister, 1838, Prisopus spiniceps Burmeister, 1838 and Prisopus cornutus Gray, 1835 are synonymised with Prisopus ohrtmanni (Lichtenstein, 1802) (n. syn.); the genus Planudes Stål, 1875 is synonymised with Isagoras Stål, 1875 (n. syn.); Pseudophasma annulipes (Redtenbacher, 1906) is synonymised with Pseudophasma blanchardi (Westwood, 1859) (n. syn.); Ignacia appendiculatum (Kirby, 1904) is synonymised with Anarchodes atrophicus (Pallas, 1772) (n. syn.). Isagoras obscurum Guérin-Méneville, 1838 is shown to have been erroneously synonymised with Isagoras rugicollis (Gray, 1835) and is here re-established as a valid species (rev. stat.). Pseudophasma castaneum (Bates, 1865) is re-established as a valid species here (rev. stat.). Paraprisopus Redtenbacher, 1906 and the entire tribe Paraprisopodini are transferred to Pseudophasmatidae: Pseudophasmatinae (n. comb.). Lectotypes are designated for Perliodes grisescens Redtenbacher, 1906, Isagoras plagiatus Redtenbacher, 1906. Neotypes are designated for Agrostia cinerea (Olivier, 1792), Prexaspes ambiguus (Stoll, 1813), Prisopus horridus (Gray, 1835) and Prisopus sacratus (Olivier, 1792).